Health-Related Quality of Life in Predominantly Young Parental Living Liver Donors: A Cross-Sectional Study in China - Shi, Yue-Xian; Zhang, Hai-Ming; Chen, Jing; Huang, Ya-Qi; Yu, Ming-Ming; Jin, Yin-Hui; Wang, Wen-Ru; Gao, Wei (Frontiers in Medicine, 2021)
Objective The health-related quality of life of donors deserves attention and must be considered for a long time. Many of the published studies had small sample sizes, and research from mainland China is scant. This study aimed to investigate the health-related quality of life of living liver donors and identify the influencing factors of the health-related quality of life in mainland China. Methods This is a cross-sectional study. The data were collected from liver transplantation center, the Tianjin First Center Hospital, China. Living liver donors older than 18 years and at a minimum of one month post donation were included. The health-related quality of life was evaluated using the Medical Outcome Study Short form 36 (SF-36). Sociodemographic- and clinical-related variables, health-related quality of life status and its potential impact factors were analyzed. Result A total of 382 living liver donors completed the survey. The median number of months post donation was 25, and parental donors (89.5%) were the most frequent relationship. The majority of participants (372, 97.4%) donated left lateral lobe. Thirty two (8.4%) donors suffered complications, and of them, biliary leakage 7 (1.8%) was the most common one in this study. The physical functioning, role–physical, bodily pain, general health, social functioning, role–emotional and mental health scores among living liver donors were significantly better than those of the Chinese norms. Short time post-donation [odds ratio (OR): 0.009; P < 0.001] and male recipients (OR: 0.197; P <0.024) were associated with the likelihood of a poor physical related quality of life. Conclusions Despite generally good health-related quality of life outcomes, we also believe that liver donation has an obvious influence on the physical function of liver donors. More attention and long-term follow-up are necessary for donors at higher risk based on identified influencing factors and correlates.